2016
DOI: 10.1364/oe.24.012442
|View full text |Cite
|
Sign up to set email alerts
|

Demanding response time requirements on coherent receivers due to fast polarization rotations caused by lightning events

Abstract: Lightning events can cause fast polarization rotations and phase changes in optical transmission fibers due to strong electrical currents and magnetic fields. Whereas these are unlikely to affect legacy transmission systems with direct detection, different mechanisms have to be considered in systems with local oscillator based coherent receivers and digital signal processing. A theoretical analysis reveals that lightning events can result in polarization rotations with speeds as fast as a few hundred kRad/s. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…The update requirements of the dynamic equalizer depends, to a large degree, on the speed of the polarization fluctuations occurring in the fiber. Following extreme changes in the surrounding environment, such as lightening strikes, the state of polarization (SOP) can fluctuate very fast [39]. However, long-term measurements of SOP-changes in installed fiber indicates much slower changes [40].…”
Section: Dynamic Equalizationmentioning
confidence: 99%
“…The update requirements of the dynamic equalizer depends, to a large degree, on the speed of the polarization fluctuations occurring in the fiber. Following extreme changes in the surrounding environment, such as lightening strikes, the state of polarization (SOP) can fluctuate very fast [39]. However, long-term measurements of SOP-changes in installed fiber indicates much slower changes [40].…”
Section: Dynamic Equalizationmentioning
confidence: 99%
“…In the polarization attack, we have switched off the intrusion signal and activated the polarization state modulator. In this operating condition, all the optical parameters of the system are the same as the baseline condition, but the polarization modulation causes transmission errors when the coherent receiver's polarization recovery algorithm is unable to track the fast polarization changes [40]. Similarly to the out-of-band attack, the polarization attack affects all the coherent OChs traversing the link where polarization modulation is applied.…”
Section: Polarization Modulation Attackmentioning
confidence: 99%
“…It has been shown that frequency-domain (FD) equalization, utilizing the fast Fourier transform (FFT), is more efficient than time-domain (TD) implementation [6][7][8][9][10]. However, in a practical real-time implementation of an adaptive equalizer with block-based processing, filter update delays will be induced due to the FFTs and other DSP operations in the feedback loop, which can degrade the equalizer's tracking ability, particularly during rapid SOP fluctuations [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%